The Socialization of Healthy Snack and Management of Pocket Money to Increase the Interest in Saving from Early Age in SDN Dumajah 1 Bangkalan - Kholid Albar; Lidia Aditama Putri; Wiwik Saidatur Rolianah; Luluk Yuliati (OJS Universitas Muhammadiyah Gresik, 2021)
In Indonesia, the society’s awareness of saving is still low, even though the public saving ratio is an indicator of the level of economic growth. It is important to introduce a culture of saving and investing from early age to foster good habits until the child grows up. The purpose of this community service activity is to increase children's interest in saving from an early age and to educate students about healthy snack. The method used in this activity was through multidisciplinary counseling in the health aspect of healthy snack and in the economic aspect of management of pocket money in order to raise awareness to consume healthy snack and to increase student’s interest in saving because it has reduced consumption of unhealthy snacks. A total of 33 students of SDN Dumajah 1 Bangkalan were targeted in this socialization. The results obtained after the socialization were that knowledge about healthy snacks increased from 9,1% to 36,4%, while students' interest in saving increased sharply from 0% to 87,9%. The follow-up evaluation carried out 6 months after the socialization showed good results where the students previously did not have savings, now even all of them have savings with most of the nominal around Rp. 500,000, - to Rp. 700,000, -. It’s means that multidisciplinary extension activities are effective in increasing children's interest in saving.